Analysis for policy to overcome barriers to reducing the prevalence of vitamin a deficiency among children (15-23 months) in Iran - Golnaz Rajaeieh; Amirhossein Takian; Naser Kalantari; Fatemeh Mohammadi-Nasrabadi (BMC, 2021)
Abstract Background About 30% of children < 5 years old are estimated to experience vitamin A deficiency worldwide. Globally, vitamin A deficiency can be reduced by five major interventions: supplementation, dietary modification, fortification, promotion of both public health, and breastfeeding. This prospective policy analysis (Prospective policy analysis focuses on the future outcomes of a proposed policy. Adapted from Patton, CV, and Sawicki DS. Basic Methods of Policy Analysis and Planning, Prentice-Hall, Inc. New Jersey,1993). (Patton A, Carl V, and David S. Basic methods of policy analysis and planning, prentice-hall, 3th ed. 2012) aimed to identify evidence-based policy options to minimize prevalence (VAD) among 15-23 months-children in Iran. Methods Thirty-eight semi-structured face-to-face interviews were held with experts at high, middle, and low managerial levels in Iran's health system, as well as at Schools of Nutrition Sciences and dietetics, using purposive and snowball sampling. All interviews were recorded by a digital voice recorder and then transcribed, codified, and eventually analyzed using a mixed approach (inductive-deductive) by MAXQDA software version 10. Results Most policies related to VAD reduction in this age group are supplementation, expansion of education, and awareness. Three main factors affecting VAD reduction policies emerged from the analysis: basic factors (governance, infrastructure, and organization), underlying factors (social factors, economy), and immediate factors (services). Due to its cross-sectoral nature, evaluating the results of the implementation of this policy requires strong and coherent inter-sectoral cooperation. The existing primary healthcare network (PHC) is a crucial means for successful implementation of policies to address VAD in Iran. Conclusions In addition to supplementation and assistance in this age group, other policies should be also planned to reduce VAD in various regions. In addition to the Ministry of Health & Medical Education (MoHME), other actors need to be involved, we advocate, throughout the entire policymaking process of policy-making to reduce VAD in Iran.